About the method of soil investigation by dilatometer Marchetti - Soltanov Канат (Рroblems of engineering and professional education, 2023)
This article is devoted for a novel to Kazakhstan field method of soil investigation - the Marchetti testing by flat and seismic dilatometer, as well as advantages and necessity of its application in the Republic of Kazakhstan.